Effects of hydrocarbon pollution in the structure of macrobenthic assemblages from two large estuaries in Brazil. Issue 1 (15th December 2017) - Camargo, Manuela Zeglin; Sandrini-Neto, Leonardo; Carreira, Renato S.; Camargo, Maurício G.
Abstract: Changes in the structure of benthic macrofauna and its relationship with hydrocarbon contamination were determined at different spatial scales in sublittoral sediments of two large estuaries in Brazil. Guanabara Bay (GB) is a heavily polluted estuary due to the presence of a large industrial complex and high demographic density. Laranjeiras Bay (LB) lies in an Environmental Protection Area and can still be considered as preserved from human activities. Despite some spatial differences within each bay, the PAHs concentrations were significantly and consistently higher in GB, with values generally above the threshold effect levels. No signs of hydrocarbon contamination were observed in LB. Macrofauna abundance, diversity and overall assemblage structure were largely different between bays. Canonical analysis of principal coordinates (CAP), used to model the relationship between macrofauna and PAHs levels, indicated that this class of hydrocarbons is the main structuring factor of soft-bottom assemblages in both bays. Highlights: We assessed macrofauna distribution at different scales in two large bays in Brazil. We modelled changes in assemblage structure along a PAH contamination gradient. Abundance, diversity and assemblage structure were largely different between bays. There was a strong relationship between soft-bottom macrofauna and PAH concentration.